2006
DOI: 10.1016/s0022-5347(06)00260-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Neoadjuvant Hormonal Therapy on the Outcome of Laparoscopic Radical Prostatectomy: A Matched Pair Analysis

Abstract: There was no significant difference with respect to operative or postoperative parameters in patients undergoing neoadjuvant androgen ablation therapy compared to controls. At centers where there is experience laparoscopic radical prostatectomy can be safely performed in patients who have undergone neoadjuvant hormonal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
0
11
2
Order By: Relevance
“…Brown et al (2004) described 0% positive surgical margins in Wve patients who received androgen deprivation before LRP compared to 17% in 60 without hormonal treatment. However, Maldonado-Valadez et al (2006) recently did not see any diVerence in the rate of positive surgical margins between 3-month NHT group and direct LRP group (18% vs. 16%, P = 1.000). The study group matched patients according to pathological stage and considered there is minor impact of neoadjuvant hormonal deprivation on positive surgical margins.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Brown et al (2004) described 0% positive surgical margins in Wve patients who received androgen deprivation before LRP compared to 17% in 60 without hormonal treatment. However, Maldonado-Valadez et al (2006) recently did not see any diVerence in the rate of positive surgical margins between 3-month NHT group and direct LRP group (18% vs. 16%, P = 1.000). The study group matched patients according to pathological stage and considered there is minor impact of neoadjuvant hormonal deprivation on positive surgical margins.…”
Section: Discussionmentioning
confidence: 93%
“…Injury to the epigastric vessels, postoperative ileus, hemoperitoneum, acute urinary retentions, anastomotic leakages, anastomotic stricture, hydrocele and urinary tract infections were observed. Brown et al (2004) compared 5 patients who did and 60 who did not receive neoadjuvant hormonal -Valadez et al (2006) evaluated the eVect of 3-month NHT on LRP operative and postoperative parameters through a matched pair analysis. There were no signiWcant diVerences between the neoadjuvant and non-neoadjuvant groups with respect to mean operative time, mean blood loss, transfusion rate, median catheter time, the complication rate and diYcult dissection level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they had no follow-up data as to whether or not prolonged (8-months) NHT prior to LRP altered BCR rates. Table 3 reviews the impact of NHT prior to LRP on PSM and BCR rate [6,7,16-18]. Brown et al [7] studied the safety and efficacy of LRP after NHT.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, inflammation caused by this apoptotic change might make surgical exfoliation of tissues difficult by causing adhesion between the prostate and prostate capsule or prostate capsule and peri-prostatic fascia 35. Regarding the effects of NHT on operative procedures in RRP, Yang, et al36 stated that a mean of 3 months of NHT led to longer surgical times than those required for the RRP-alone group, while Selli and Milesi25 reported that NHT did not cause any adverse surgical events.…”
Section: Discussionmentioning
confidence: 99%